The Effects of Total Health Expenditure on Economic Growth in Central and Eastern Sub-Sahara African Regions - Faith Yusufu; Olanike Bosede Awoyemi; Kehinde John Komolafe (Yayasan Riset dan Pengembangan Intelektual, 2022)
This study looked at the link connecting the growth of the economy and health spending in Central and Eastern Sub-Saharan Africa. To assess the short and long-term effects of total per capita health expenditure on the growth of the economy across Sub-Saharan African areas (East Africa and Central Africa), the panel data analysis was employed. In the short-term, total per-capita health expenditure (THE_PC) in Central Africa has an upbeat outcome on economic growth (LGDP_PC) at all levels of significance. In the long-term, current health per-capital expenditure (CHE_PC) has an upbeat outcome on the growth of the economy (LGDP_PC) at 5% and 10% significance levels, whereas life expectancy at birth (LEB) has a downbeat outcome on the growth of the economy. In East Africa THE_PC in the short and long-run has a favorable effect on the growth of the economy (LGDP_PC) at 5 and 10% significant levels, whereas CHE_GDP has a downbeat outcome on the growth of the economy (LGDP_PC) at all levels in the long-run. The findings imply that increasing per-capita health spending will boost the growth of the economy in the short term while increasing CHE_PC and LEB will boost economic growth in the long run. More investment in health services is recommended. Keywords: Public Spending, Economic Growth, GDP Per-Capita, Long Run, Mean Group, Dynamic Fixed Effect, Pooled Mean Group/ARDL (Autoregressive Distributed Lags), Short Run